Body Complexion and Circulating Lipids in the Risk of TDP-43 Related Disorders - Esteban-García, Noelia; Fernández-Beltrán, Luis C.; Godoy-Corchuelo, Juan Miguel; Ayala, Jose L.; Matias-Guiu, Jordi A.; Corrochano, Silvia (Frontiers in Aging Neuroscience, 2022)
Objective: Frontotemporal dementia (FTD) and Amyotrophic lateral sclerosis (ALS) are two distinct degenerative disorders with overlapping genetics, clinical manifestations and pathology, including the presence of TDP-43 aggregates in nearly 50% of FTD patients and 98% of all ALS patients. Here, we evaluate whether different genetically-predicted body lipid metabolic traits are causally associated with the risk of FTD TDP43 subtype, and compare it to their causal role in the risk of ALS, and identify genetic variants shared between these two TDP43 related disorders in relation to lipid metabolic traits. Methods: We conducted two-sample mendelian randomization analyses (2SMR) to evaluate the causal association of 9 body complexion and 9 circulating lipids traits with the risk of FTD TDP43 subtype, and the risk of ALS. The inverse-variance weighted method was the primary analysis followed by secondary sensitive analyses. We then looked for common genetic variants between FTD TDP43 subtype and ALS in relation to lipid metabolic traits. Results: Genetically increased trunk predicted mass, fat-free mass and higher circulating triglycerides levels were suggestively associated with higher risk of FTD TDP43 subtype. Circulating lipids, mainly LDL cholesterol, were causally associated with higher risk of ALS. We identified two genetic variants, EIF4ENIF1 and HNRNPK, in relation to body complexion and circulating lipids shared between FTD TDP43 subtype and ALS. Conclusions: This work provides evidence that body complexion and circulating lipids traits impact differentially on the risk of FTD TDP43 subtype and ALS, suggesting new and specific interventional approaches in the control of body lipid metabolism for FTD and ALS, and identified HNRNPK as a potential link between circulating lipids levels and these disorders.